Did California's Shelter-In-Place Order Work? Early Coronavirus-Related Public Health Effects - Andrew I. Friedson; Drew McNichols; Joseph J. Sabia; Dhaval M. Dave (Institute of Labor Economics (IZA), 2020)
On March 19, 2020, California Governor Gavin Newsom issued Executive Order N-33-20 2020, which required all residents of the state of California to shelter in place for all but essential activities such as grocery shopping, retrieving prescriptions from a pharmacy, or caring for relatives. This shelter-in-place order (SIPO), the first such statewide order issued in the United States, was designed to reduce COVID-19 cases and mortality. While the White House Task Force on the Coronavirus has credited the State of California for taking early action to prevent a statewide COVID-19 outbreak, no study has examined the impact of California's SIPO. Using daily state-level coronavirus data and a synthetic control research design, we find that California's statewide SIPO reduced COVID-19 cases by 125.5 to 219.7 per 100,000 population by April 20, one month following the order. We further find that California's SIPO led to as many as 1,661 fewer COVID-19 deaths during the first four weeks following its enactment. Back-of-the-envelope calculations suggest that there were about 400 job losses per life saved during this short-run post-treatment period.
Keywords: H75; I18; 330; coronavirus; COVID-19; synthetic control; shelter in place order